Solving the statistical test selection problem in hypothesis testing / Foo Kien-Kheng... [et al.] - Kien-Kheng, Foo; Azlan, Nuralina; Idris, Noraini; Ahmad, Siti Noor Dina (Universiti Teknologi MARA, Negeri Sembilan, 2016)
Hypothesis testing is widely regarded as a valuable tool for data analysis but it is conceptually difficult to understand and even more difficult to carry out the procedure. Even so, interpretation of the results is often littered with mistakes and misuses. This paper proposes an approach through the use of STestMAP. It is a tool resembling a concept map designed to assist researchers in identifying relevant univariate statistical tests to match their research objectives. An earlier study in the efficacy of this approach as a tool to acquire selection skills has shown STestMAP provides a flexible structure in assisting users to successfully identify the statistical test but further research is needed to confirm the usefulness of STestMAP.